Analisis Sistem Akuntansi Penggajian Pada Koperasi Petani Tebu Rakyat Sari Rosan Kab. Mojokerto - Azizah Siska Apriliana; Dyah Pravitasari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the Payroll Accounting System in the Sugarcane Farmers Cooperative Sari Rosan Kab. Mojokerto. The research method used in this research is descriptive qualitative. Data collection techniques with the method of observation, interviews, and documentation. The results showed that the Sugar Cane Farmers Cooperative Sari Rosan Kab. Mojokerto has an analysis of the payroll accounting system applied. The implementation of the payroll accounting system carried out by the company can be seen from the preparation of the organization that has involved all parts of both subordinates and superiors. Meanwhile, when viewed from the organizational structure, the company has given authority and responsibility to every part of the organization.